THERMODYNAMIC PROPERTIES OF BARU FRUITS (Dipteryx alata Vogel) - Resende,Osvaldo (2017)
ABSTRACT: The objective of this study was to determine and evaluate the thermodynamic properties for different equilibrium moisture contents in baru fruits (Dipteryx alata Vogel), using the direct static method to obtain the experimental data. The Modified Halsey model was used to determine the thermodynamic properties of baru fruits. Results concluded that thermodynamic properties are influenced by moisture content. The water vaporization latent heat increases with the decrease in equilibrium moisture content. The baru fruit desorption process is controlled by enthalpy. Gibbs free energy is positive for the temperatures studied with the increase over desorption, which describes a non-spontaneous process.